2015
DOI: 10.1007/s12254-015-0216-6
|View full text |Cite
|
Sign up to set email alerts
|

Esthesioneuroblastoma metastatic to the neck and lung: a case report and review of the literature

Abstract: Esthesioneuroblastoma (ENB) is a rare tumor of the olfactory epithelium that has been shown to metastasize mostly to the lymph nodes of the neck but more rarely to other locations. We report on a rare case characterized by distant metastasis to the neck and lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The sites of distant metastasis reported in various large scale and single case reports are brain, spinal cord, meninges, bone, bone marrow, lung, liver, dermal, breast, heart, parotid and thyroid gland [9][10][11][12][13][14][15][16][17][18][19][20][21] and Table 1. Buohliqa et al [18] have reported three unusual recurrences, distinctly distant from the primary site, raising the questions of what constitutes real recurrence versus embolic metastasis especially around the paranasal sinuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sites of distant metastasis reported in various large scale and single case reports are brain, spinal cord, meninges, bone, bone marrow, lung, liver, dermal, breast, heart, parotid and thyroid gland [9][10][11][12][13][14][15][16][17][18][19][20][21] and Table 1. Buohliqa et al [18] have reported three unusual recurrences, distinctly distant from the primary site, raising the questions of what constitutes real recurrence versus embolic metastasis especially around the paranasal sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…During radiotherapy Mrad et al 2005 11 1 Breast 2 years Bachar et al 2008 12 3/39 Bone, lung, retroperitoneum Up to 39 months later Mattavelli et al 2009 13 1 Trachea 18 months Chew et al 2011 14 1 17 1 Neck and left lung nodule 2 years Buohliqa et al 2015 18 3/3 Maxillary sinus (2), sphenoid sinus (1) 51 months -7 years Banuchi et al 2016 19 13/57 CNS (6), bone (3), leptomeningeal (4), dermal (1) 9-134 months Hussaini et al 2016 20 1 Parotid gland 30 and 40 months Rahman M et al 2017 21 1 Thyroid gland 7 years Current study 2019 1 Submandibular gland 5 months prior to primary diagnosis…”
Section: Studymentioning
confidence: 99%
“…In all studies included in this review, this finding has been consistent regardless of the resection type. This finding becomes more apparent with higher disease stages as surgery followed by radiation therapy showed longer disease-free progression in Kadesh stage C in particular [25-28].…”
Section: Reviewmentioning
confidence: 99%